The Role of Basolateral Amygdalar Cholinergic Neuromodulation in Emotional Learning - Victor Manuel Torres-Garcia; Emmanuel Rodriguez-Nava; Gabriel Roldan-Roldan; Donald B. Katz; Jean-Pascal Morin (Journal of Integrative Neuroscience, 2025)
The basolateral amygdala (BLA) is crucial for assigning emotional valence to sensory experiences, driving approach or avoidance behaviors during subsequent encounters. Particularly, the BLA plays a critical role in the coding, storage and retrieval of emotional learning. While traditionally viewed through the lens of memory consolidation, cholinergic signaling—mediated by dense inputs from the basal forebrain and abundant muscarinic receptors (mAChRs) in the BLA—plays a far more dynamic role. Acetylcholine, often described as a “memory molecule”, is central to this process, with scopolamine induced amnesia models underscoring its importance. Recent evidence suggests that cholinergic activity not only supports memory formation but also imparts emotional valence under specific conditions. This review examines the molecular and cellular mechanisms by which mAChR-mediated cholinergic signaling modulates BLA processing and the storage of emotional memories. We integrate psychopharmacological insights with loss and gain-of-function studies to demonstrate how cholinergic signaling in the BLA shapes approach and avoidance behaviors. Based on this evidence, we propose that acetylcholine’s influence in the BLA is highly context-dependent, reflecting its versatile role in emotional processing beyond mere memory consolidation.